Re-performance: a critical and reparative methodology for everyday expertise and data practice in policy knowledge - Susan Oman (International Review of Public Policy)
This paper introduces and develops an innovative re-performance methodology to reappraise tensions in evidence-based policy-making (EBPM). It conceptualises ‘re-performance’ as re-enacting and/or replicating aspects of another’s research, extending analyses of default, established methods of knowledge-for-policy. Re-performance is an under-utilised concept and this paper synthesises its assorted origins across humanities disciplines to demonstrate its conceptual utility for methods in research on research. Application of the re-performance methodology involves drawing from content analyses and ethnographic methods to understand the context of knowledge production as cultural production, and critical theory lenses to analyse these effects. The methodology was developed over two research projects on well-being and inequality metrics; both are presented to establish this approach as one that was developed in contestation over data and everyday knowledge (Case 1), that can be applied in a way that is reparative (Case 2), and consequently is of use to understanding current international data-policy controversies and crises. Overall, this article demonstrates re-performance as a methodology that recognises complexity in incorporating the social practices of everyday knowledge and expertise in a framework for policy studies in which the focus on data-in-research as performative reveals the effects in and on the cultures they describe.